Preparation method of a reusable flexible aerogel composite material with hydrophobic performance resistant to 800°C

Through the combination of surface-modified alumina whiskers and nanoalumina whiskers and ethyl silicate, combined with multiple impregnation and vapor deposition processes, the poor strength, flexibility and hydrophobicity of silica aerogels at high temperatures are solved. The problem of this is that the high-performance thermal insulation effect of flexible aerogel composite material with a resistance to 800°C is achieved.

CN118791292BActive Publication Date: 2024-12-13SHANDONG RES & DESIGN ACADEMY OF IND CERAMICS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411284582.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-13
Publication Date
2024-12-13
Estimated Expiration
2044-09-13

AI Technical Summary

Technical Problem

Existing silica aerogels exhibit low strength, poor flexibility, poor hydrophobicity and poor durability at high temperatures, resulting in a degradation of thermal insulation performance.

Method used

By combining the preparation of surface-modified alumina whiskers and nano-alumina whisker suspensions and ethyl silicate and other materials, multiple impregnation and vapor deposition processes are used to form a reusable flexible gas with a hydrophobic performance of 800°C. Gel composite material.

Benefits of technology

The strength, flexibility, hydrophobicity and high temperature resistance of the aerogel composite material are improved, and the compressive strength, tensile strength and thermal conductivity of the room temperature are significantly improved, and good thermal insulation performance is maintained at 800℃.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a method for preparing a reusable flexible aerogel composite material with hydrophobicity resistant to 800°C, belonging to the technical field of aerogel composite materials. The preparation method comprises the following steps: preparing a first sol, preparing a second sol, pretreatment, primary impregnation, secondary impregnation, and vapor deposition; the preparation of the first sol comprises the following steps: preparing a surface-modified alumina whisker suspension, and mixing; the preparation of the second sol comprises the following steps: preparing a surface-modified nano alumina whisker suspension, and mixing; the preparation method of the invention can improve the strength, flexibility, hydrophobicity, durability and high temperature resistance of the flexible aerogel composite material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of aerogel composite materials, and in particular to a method for preparing a reusable flexible aerogel composite material with hydrophobic properties and resistant to 800°C. Background Art

[0002] Aerogel is a nano-scale porous solid material formed by replacing the liquid phase in the gel with gas through a sol-gel method and a certain drying method. Aerogel has extremely high porosity and extremely low thermal conductivity. It is a lightweight, high-temperature resistant, and efficient thermal insulation material. Aerogel exhibits excellent performance in thermal, electrical, optical, acoustic, adsorption and catalytic aspects, making aerogel have broad application prospects in aerospace, building energy conservation, chemical industry, electronic and electrical engineering, biomedicine and other fields.

[0003] Aerogels mainly include silicon-based aerogels, carbon-based aerogels, sulfur-based aerogels, metal-based aerogels, metal oxide-based aerogels, etc. At present, silicon-based aerogels are the most widely used. Silicon-based aerogels mainly refer to silica aerogels. The silicon source used in silica aerogels is sodium silicate. In the sol-gel process, sodium silicate reacts with acid to form aerogels. At present, organic alcohol salts are mainly used as raw materials in the preparation of silica aerogels. Among them, the most commonly used organic alcohol salt is ethyl orthosilicate.

[0004] However, silica aerogel has the disadvantages of low strength, poor flexibility and hydrophobicity, which affect the application effect of silica aerogel. In order to improve the strength of silica aerogel, the most commonly used method is to add ceramic fibers to silica aerogel, but the addition of ceramic fibers will further reduce the flexibility of silica aerogel and cause the silica aerogel to easily fall off, which further leads to poor durability of silica aerogel and serious decline in thermal insulation performance under high temperature for a long time; in order to improve the flexibility of silica aerogel, the most commonly used method is to add a fiber reinforcement phase with good continuity to silica aerogel, but the compatibility between silica aerogel and the fiber reinforcement phase is poor. This results in poor bonding strength and easy powder loss problems, which in turn leads to poor durability of the silica aerogel, and a serious decline in thermal insulation performance when exposed to high temperatures for a long time. In order to improve the hydrophobicity of silica aerogel, the most commonly used method is to hydrophobically modify the silica aerogel, specifically using hydrophobic organic functional groups to replace the hydrophilic hydroxyl groups on the surface of the silica aerogel. However, the introduced hydrophobic organic functional groups are easily broken after being heated, resulting in a decrease in hydrophobicity, which further leads to poor high temperature resistance of the hydrophobically modified silica aerogel, and a serious decline in hydrophobic performance when exposed to high temperatures for a long time.

[0005] Therefore, developing an aerogel composite material with high strength, good flexibility and hydrophobicity, as well as good durability and high temperature resistance is an urgent problem to be solved. Summary of the invention

[0006] In view of the shortcomings of the prior art, the present invention provides a method for preparing a reusable flexible aerogel composite material with hydrophobic properties resistant to 800°C, which can improve the strength, flexibility, hydrophobicity, durability and high temperature resistance of the flexible aerogel composite material.

[0007] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:

[0008] A method for preparing a reusable flexible aerogel composite material with hydrophobic properties resistant to 800°C, comprising the following steps: preparing a first sol, preparing a second sol, pre-treating, impregnating once, impregnating twice, and vapor deposition;

[0009] The preparation of the first sol comprises the following steps: preparing a surface-modified aluminum oxide whisker suspension, mixing;

[0010] The surface-modified aluminum oxide whisker suspension is prepared by mixing aluminum oxide whiskers, polysorbate 80, and a first portion of deionized water, stirring at room temperature at a stirring speed of 100-200 rpm for 3-4 hours, centrifuging, taking a precipitate, washing it with deionized water for 3-4 times, vacuum drying, mixing it with a second portion of deionized water, and ultrasonically oscillating it at a frequency of 20-25 kHz for 25-35 minutes to obtain a surface-modified aluminum oxide whisker suspension;

[0011] In the preparation of the surface-modified aluminum oxide whisker suspension, the mass volume ratio of the aluminum oxide whisker, polysorbate 80, the first portion of deionized water, and the second portion of deionized water is 100-120 g: 30-35 g: 2200-2500 mL: 1200-1300 mL;

[0012] The average length of the aluminum oxide whiskers is 10 μm and the average diameter is 0.5 μm;

[0013] The first sol is prepared by mixing tetraethyl orthosilicate, anhydrous ethanol and deionized water, stirring at room temperature at a stirring speed of 100-200 rpm for 10-15 minutes, adding hydrochloric acid aqueous solution to adjust the pH to 3-4, stirring for 2-2.5 hours, and dropping the surface modified aluminum oxide whisker suspension. After the dropping is completed, stirring is continued for 30-40 minutes to obtain a first sol;

[0014] In the mixing for preparing the first sol, the volume ratio of ethyl orthosilicate, anhydrous ethanol, deionized water, and surface-modified alumina whisker suspension is 400-420:1800-2100:160-180:120-140;

[0015] The concentration of the hydrochloric acid aqueous solution is 0.1 mol / L;

[0016] The drop rate of the surface modified aluminum oxide whisker suspension is 4-5 mL / min;

[0017] The preparation of the second sol comprises the following steps: preparing a surface-modified nano-aluminum oxide whisker suspension, mixing;

[0018] The surface-modified nano-aluminum oxide whisker suspension is prepared by mixing nano-aluminum oxide whiskers, polysorbate 80, and a first portion of deionized water, stirring at room temperature at a stirring speed of 100-200 rpm for 3-4 hours, centrifuging, taking a precipitate, washing it with deionized water for 3-4 times, vacuum drying, mixing it with a second portion of deionized water, and ultrasonically oscillating it at a frequency of 20-25 kHz for 40-50 minutes to obtain a surface-modified nano-aluminum oxide whisker suspension;

[0019] In the preparation of the surface-modified nano-aluminum oxide whisker suspension, the mass volume ratio of the nano-aluminum oxide whisker, polysorbate 80, the first portion of deionized water, and the second portion of deionized water is 100-120 g: 45-50 g: 2900-3200 mL: 1600-1800 mL;

[0020] The average length of the nano-aluminum oxide whiskers is 200 nm and the average diameter is 10 nm;

[0021] The preparation of the second sol comprises mixing tetraethyl orthosilicate, anhydrous ethanol and deionized water, stirring at room temperature at a stirring speed of 100-200 rpm for 10-15 minutes, adding a hydrochloric acid aqueous solution to adjust the pH to 3-4, stirring for 2-2.5 hours, dropping a surface-modified nano-aluminum oxide whisker suspension, and continuing to stir for 30-40 minutes after the dropping is completed to obtain a second sol;

[0022] In the mixing for preparing the second sol, the volume ratio of ethyl orthosilicate, anhydrous ethanol, deionized water, and surface-modified nano-aluminum oxide whisker suspension is 400-420:1800-2100:160-180:170-200;

[0023] The concentration of the hydrochloric acid aqueous solution is 0.1 mol / L;

[0024] The drop rate of the surface modified nano-alumina whisker suspension is 5-6 mL / min;

[0025] The pretreatment comprises completely immersing the three-dimensional alumina fiber fabric in a polyethylene glycol 400 aqueous solution, standing at room temperature for 4-5 hours, taking it out, washing it with deionized water for 3-4 times, and vacuum drying it to obtain a fiber fabric treated with polyethylene glycol, mixing the fiber fabric treated with polyethylene glycol, 1,2-butanediol, 3-aminopropyltrimethoxysilane, and p-toluenesulfonic acid, stirring it at 90-95° C. at a stirring speed of 200-300 rpm for 30-40 minutes, stirring it at 150-155° C. for 8-9 hours, taking out the three-dimensional alumina fiber fabric, washing it with deionized water for 3-4 times, washing it with anhydrous ethanol for 3-4 times, and standing it to obtain a pretreated three-dimensional alumina fiber fabric;

[0026] In the pretreatment, the mass volume ratio of the polyethylene glycol-treated fiber fabric, 1,2-butanediol, 3-aminopropyltrimethoxysilane, and p-toluenesulfonic acid is 500-520 g: 1500-1600 mL: 950-1050 mL: 15-20 g;

[0027] The concentration of the polyethylene glycol 400 aqueous solution is 5wt%;

[0028] The fiber volume fraction in the three-dimensional alumina fiber fabric is 40%;

[0029] The static temperature is 55-60°C, the pressure is 1-2kPa, and the time is 35-40min;

[0030] The primary impregnation is to perform vacuum pretreatment on the pretreated three-dimensional alumina fiber fabric, then completely immerse it in the first sol with the initiator added thereto for vacuum treatment, dry it, take it out and completely immerse it in anhydrous ethanol for aging, take it out and perform supercritical drying, after the supercritical drying is completed, release the gas and naturally cool it to room temperature, take it out and let it stand, to obtain the fiber fabric after the primary impregnation;

[0031] In the first dipping, the preparation method of the first sol with the added initiator is: adding ammonia water to the first sol to adjust the pH to 6-7, so as to obtain the first sol with the added initiator;

[0032] The concentration of the ammonia water is 0.5-1 mol / L;

[0033] The vacuum pretreatment has a vacuum pressure of -0.095 MPa to -0.1 MPa and a time of 30-40 min;

[0034] The vacuum pressure of the vacuum treatment is -0.095MPa to -0.1MPa, and the time is 50-60min;

[0035] The drying temperature is 50-70°C and the drying time is 5-8h;

[0036] The aging temperature is 30-60° C., the time is 48-72 hours, and the anhydrous ethanol is replaced once every 12 hours during the aging process;

[0037] The supercritical drying is carried out in a nitrogen atmosphere at a temperature of 260-280° C., a pressure of 8-10 MPa, and a time of 1-3 h;

[0038] The standing temperature is 600-700°C and the time is 1.5-2h;

[0039] The secondary impregnation is to perform vacuum pretreatment on the fiber fabric after the primary impregnation, then completely immerse it in the second sol with the initiator for vacuum treatment, dry it, take it out and completely immerse it in anhydrous ethanol for aging, take it out and perform supercritical drying, release the gas after the supercritical drying and naturally cool it to room temperature, take it out and let it stand, so as to obtain the fiber fabric after the primary impregnation;

[0040] In the secondary impregnation, the second sol with the initiator added is prepared by adding ammonia water to the first sol to adjust the pH to 6-7 to obtain the second sol with the initiator added;

[0041] The concentration of the ammonia water is 0.5-1 mol / L;

[0042] The vacuum pretreatment has a vacuum pressure of -0.095 MPa to -0.1 MPa and a time of 30-40 min;

[0043] The vacuum pressure of the vacuum treatment is -0.095MPa to -0.1MPa, and the time is 70-80min;

[0044] The drying temperature is 60-70°C and the drying time is 5-8h;

[0045] The aging temperature is 30-60° C., the time is 48-72 hours, and the anhydrous ethanol is replaced once every 12 hours during the aging process;

[0046] The supercritical drying is carried out in a nitrogen atmosphere at a temperature of 260-280° C., a pressure of 8-10 MPa, and a time of 1-3 h;

[0047] The standing temperature is 600-700°C and the time is 2-3h;

[0048] The vapor deposition is to add the fiber fabric after the secondary impregnation into a chemical vapor deposition furnace, evacuate, raise the temperature to 800-1000°C, introduce BCl3, NH3, H2, and Ar into the reaction chamber, and feed gas for 30-40 minutes to obtain a flexible aerogel composite material with hydrophobic performance resistant to 800°C and reusable;

[0049] In the vapor deposition, the heating rate to 800-1000°C is 25-30°C / min;

[0050] The introduction rate of the BCl3 is 0.8-1.2 L / min, the introduction rate of the NH3 is 3.2-4.8 L / min, the introduction rate of the H2 is 5 L / min, and the introduction rate of the Ar is 5 L / min.

[0051] Compared with the prior art, the present invention has the following beneficial effects:

[0052] (1) The method for preparing the 800°C hydrophobic and reusable flexible aerogel composite material of the present invention can improve the strength and flexibility of the flexible aerogel composite material. The prepared flexible aerogel composite material has a compressive strength of 1.47-1.53 ​​MPa and a tensile strength of 1.19-1.24 MPa at 10% compression.

[0053] (2) The method for preparing the reusable flexible aerogel composite material with 800°C hydrophobic resistance of the present invention can improve the hydrophobicity of the flexible aerogel composite material, and the prepared flexible aerogel composite material has a wetting angle of 148.0-149.5° at room temperature;

[0054] (3) The method for preparing the reusable flexible aerogel composite material with hydrophobic properties resistant to 800°C of the present invention can improve the durability of the flexible aerogel composite material. The room temperature wetting angle of the prepared flexible aerogel composite material after being treated at 800°C for 2 hours is 145.1-145.6°;

[0055] (4) The method for preparing a reusable flexible aerogel composite material with hydrophobic properties resistant to 800°C of the present invention can improve the high temperature resistance of the flexible aerogel composite material. The thermal conductivity of the prepared flexible aerogel composite material is 0.024-0.025 W / m·K at room temperature, 0.032-0.034 W / m·K at 800°C, and 0.026-0.029 W / m·K at room temperature after treatment at 800°C for 2 hours. DETAILED DESCRIPTION

[0056] In order to have a clearer understanding of the technical features, purposes and effects of the present invention, the specific implementation methods of the present invention are now described.

[0057] Example 1

[0058] A method for preparing a reusable flexible aerogel composite material with hydrophobic properties resistant to 800°C, specifically comprising:

[0059] 1. Preparation of the first sol:

[0060] (1) Preparation of surface modified aluminum oxide whisker suspension: 100 g aluminum oxide whisker, 30 g polysorbate 80 and 2200 mL deionized water were mixed, stirred at room temperature at a stirring speed of 100 rpm for 3 h, centrifuged, and the precipitate was collected and washed with deionized water for 3 times. After vacuum drying, the precipitate was mixed with 1200 mL deionized water, and ultrasonically vibrated at a frequency of 20 kHz for 25 min to obtain a surface modified aluminum oxide whisker suspension;

[0061] The average length of the aluminum oxide whiskers is 10 μm and the average diameter is 0.5 μm;

[0062] (2) Mixing: 400 mL of tetraethyl orthosilicate, 1800 mL of anhydrous ethanol, and 160 mL of deionized water were mixed, and stirred at room temperature at a stirring speed of 100 rpm for 10 min. A 0.1 mol / L hydrochloric acid aqueous solution was added to adjust the pH to 3, and stirred for 2 h. 120 mL of the surface-modified alumina whisker suspension was added dropwise at a dropping speed of 4 mL / min. After the addition was completed, stirring was continued for 30 min to obtain a first sol.

[0063] 2. Preparation of the second sol:

[0064] (1) Preparation of surface-modified nano-aluminum oxide whisker suspension: 100 g of nano-aluminum oxide whisker, 45 g of polysorbate 80, and 2900 mL of deionized water were mixed, stirred at room temperature at a stirring speed of 100 rpm for 3 h, centrifuged, and the precipitate was collected and washed with deionized water for 3 times. After vacuum drying, the precipitate was mixed with 1600 mL of deionized water, and ultrasonically vibrated at a frequency of 20 kHz for 40 min to obtain a surface-modified nano-aluminum oxide whisker suspension;

[0065] The average length of the nano-aluminum oxide whiskers is 200 nm and the average diameter is 10 nm;

[0066] (2) Mixing: 400 mL of tetraethyl orthosilicate, 1800 mL of anhydrous ethanol, and 160 mL of deionized water were mixed, and stirred at room temperature at a stirring speed of 100 rpm for 10 min. A 0.1 mol / L hydrochloric acid aqueous solution was added to adjust the pH to 3, and stirred for 2 h. 170 mL of the surface-modified nano-alumina whisker suspension was added dropwise at a dropping speed of 5 mL / min. After the addition was completed, stirring was continued for 30 min to obtain a second sol.

[0067] 3. Pretreatment: The three-dimensional alumina fiber fabric was completely immersed in a 5wt% polyethylene glycol 400 aqueous solution, allowed to stand at room temperature for 4h, taken out, washed 3 times with deionized water, and vacuum dried to obtain the polyethylene glycol-treated fiber fabric. 500g of the polyethylene glycol-treated fiber fabric, 1500mL of 1,2-butanediol, 950mL of 3-aminopropyltrimethoxysilane, and 15g of p-toluenesulfonic acid were mixed, stirred at 90°C at a stirring speed of 200rpm for 30min, stirred at 150°C for 8h, the three-dimensional alumina fiber fabric was taken out, washed 3 times with deionized water, washed 3 times with anhydrous ethanol, and allowed to stand for 35min at a temperature of 55°C and a pressure of 1kPa to obtain the pretreated three-dimensional alumina fiber fabric;

[0068] The fiber volume fraction in the three-dimensional alumina fiber fabric is 40%;

[0069] 4. One-time impregnation: Add the pretreated three-dimensional alumina fiber fabric into the mold, then put it into a vacuum tank, evacuate to a vacuum pressure of -0.095MPa, let it stand for 30min, then add 0.5mol / L ammonia water to the first sol to adjust the pH to 6 to obtain the first sol with added initiator, add the first sol with added initiator into the vacuum tank to ensure that the pretreated three-dimensional alumina fiber fabric is completely immersed in the first sol with added initiator, and continue to evacuate to a vacuum pressure of -0.0 The mixture was placed at 95 MPa for 50 min, taken out and dried at 50 ° C for 5 h, then taken out and completely immersed in anhydrous ethanol, placed at 30 ° C for 48 h, the anhydrous ethanol was replaced once every 12 h, taken out and added to a supercritical drying kettle, and the temperature of the supercritical drying kettle was controlled to 260 ° C and the pressure was controlled to 8 MPa under a nitrogen atmosphere. The temperature and pressure were kept for 1 h, the gas was released and the temperature was naturally lowered to room temperature, taken out and placed at a temperature of 600 ° C for 1.5 h to obtain a fiber fabric after one immersion;

[0070] 5. Secondary impregnation: Add the fiber fabric after the primary impregnation into the mold, and then put it into a vacuum tank, evacuate to a vacuum pressure of -0.095MPa, let it stand for 30 minutes, then add 0.5mol / L ammonia water to the second sol to adjust the pH to 6 to obtain the second sol with the initiator added, add the second sol with the initiator added into the vacuum tank to ensure that the pretreated three-dimensional alumina fiber fabric is completely immersed in the second sol with the initiator added, and continue to evacuate to a vacuum pressure of -0.09 5MPa environment for 70min, take out and dry at 60℃ for 5h, take out and completely immerse in anhydrous ethanol, stand at 30℃ for 48h, replace anhydrous ethanol once every 12h, take out and add to a supercritical drying kettle, control the temperature of the supercritical drying kettle to 260℃ and the pressure to 8MPa under nitrogen atmosphere, keep the temperature and pressure for 1h, release the gas and naturally cool to room temperature, take out and stand at 600℃ for 2h to obtain the fiber fabric after secondary impregnation;

[0071] 6. Vapor deposition: Add the fiber fabric after the second impregnation into a chemical vapor deposition furnace, evacuate the chamber, heat the temperature to 800°C at a rate of 25°C / min, introduce BCl3, NH3, H2, and Ar into the reaction chamber, control the introduction rate of BCl3 to 0.8L / min, the introduction rate of NH3 to 3.2L / min, the introduction rate of H2 to 5L / min, and the introduction rate of Ar to 5L / min, and feed the gas for 30 minutes to obtain a reusable flexible aerogel composite material with hydrophobic properties resistant to 800°C.

[0072] Example 2

[0073] A method for preparing a reusable flexible aerogel composite material with hydrophobic properties resistant to 800°C, specifically comprising:

[0074] 1. Preparation of the first sol:

[0075] (1) Preparation of surface modified aluminum oxide whisker suspension: 110 g aluminum oxide whisker, 32 g polysorbate 80, and 2400 mL deionized water were mixed, stirred at room temperature at a stirring speed of 150 rpm for 3.5 h, centrifuged, and the precipitate was taken out and washed with deionized water for 3 times. After vacuum drying, it was mixed with 1250 mL deionized water and ultrasonically vibrated at a frequency of 20 kHz for 30 min to obtain a surface modified aluminum oxide whisker suspension;

[0076] The average length of the aluminum oxide whiskers is 10 μm and the average diameter is 0.5 μm;

[0077] (2) Mixing: 410 mL of tetraethyl orthosilicate, 2000 mL of anhydrous ethanol, and 170 mL of deionized water were mixed, and stirred at room temperature at a stirring speed of 150 rpm for 12 min. A 0.1 mol / L hydrochloric acid aqueous solution was added to adjust the pH to 3.5, and stirred for 2 h. 130 mL of the surface-modified alumina whisker suspension was added dropwise at a dropping speed of 4 mL / min. After the addition was completed, stirring was continued for 35 min to obtain a first sol.

[0078] 2. Preparation of the second sol:

[0079] (1) Preparation of surface-modified nano-aluminum oxide whisker suspension: 110 g of nano-aluminum oxide whisker, 48 g of polysorbate 80, and 3000 mL of deionized water were mixed, stirred at room temperature at a stirring speed of 150 rpm for 3.5 h, centrifuged, and the precipitate was taken out and washed with deionized water for 3 times. After vacuum drying, it was mixed with 1700 mL of deionized water and ultrasonically vibrated at a frequency of 20 kHz for 45 min to obtain a surface-modified nano-aluminum oxide whisker suspension;

[0080] The average length of the nano-aluminum oxide whiskers is 200 nm and the average diameter is 10 nm;

[0081] (2) Mixing: 410 mL of tetraethyl orthosilicate, 2000 mL of anhydrous ethanol, and 170 mL of deionized water were mixed, and stirred at room temperature at a stirring speed of 150 rpm for 12 min. A 0.1 mol / L hydrochloric acid aqueous solution was added to adjust the pH to 3.5, and stirred for 2 h. 180 mL of the surface-modified nano-alumina whisker suspension was added dropwise at a dropping speed of 5 mL / min. After the addition was completed, stirring was continued for 35 min to obtain a second sol.

[0082] 3. Pretreatment: The three-dimensional alumina fiber fabric was completely immersed in a 5wt% polyethylene glycol 400 aqueous solution, allowed to stand at room temperature for 4.5h, taken out, washed 3 times with deionized water, and vacuum dried to obtain the polyethylene glycol-treated fiber fabric. 510g of polyethylene glycol-treated fiber fabric, 1550mL of 1,2-butanediol, 1000mL of 3-aminopropyltrimethoxysilane, and 18g of p-toluenesulfonic acid were mixed, stirred at 90°C at a stirring speed of 250rpm for 35min, stirred at 152°C for 8.5h, the three-dimensional alumina fiber fabric was taken out, washed 3 times with deionized water, washed 3 times with anhydrous ethanol, and allowed to stand for 37min at a temperature of 57°C and a pressure of 1kPa to obtain the pretreated three-dimensional alumina fiber fabric;

[0083] The fiber volume fraction in the three-dimensional alumina fiber fabric is 40%;

[0084] 4. Primary impregnation: Add the pretreated three-dimensional alumina fiber fabric into the mold, then put it into a vacuum tank, evacuate to a vacuum pressure of -0.095MPa, let it stand for 35min, then add 0.5mol / L ammonia water to the first sol to adjust the pH to 6.5 to obtain the first sol with added initiator, add the first sol with added initiator into the vacuum tank to ensure that the pretreated three-dimensional alumina fiber fabric is completely immersed in the first sol with added initiator, and continue to immerse in the vacuum pressure of -0. 095MPa environment for 55min, taken out and dried at 60℃ for 6h, taken out and completely immersed in anhydrous ethanol, and stood at 40℃ for 60h, the anhydrous ethanol was replaced once every 12h, taken out and added to a supercritical drying kettle, and under a nitrogen atmosphere, the temperature of the supercritical drying kettle was controlled to 270℃, the pressure was controlled to 9MPa, and the temperature and pressure were kept for 2h, the gas was released and the temperature was naturally lowered to room temperature, taken out and stood at a temperature of 650℃ for 1.5h, and the fiber fabric after one impregnation was obtained;

[0085] 5. Secondary impregnation: Add the fiber fabric after the primary impregnation into the mold, and then put it into a vacuum tank, evacuate to a vacuum pressure of -0.095MPa, let it stand for 35 minutes, then add 0.5mol / L ammonia water to the second sol to adjust the pH to 6.5 to obtain the second sol with added initiator, add the second sol with added initiator into the vacuum tank to ensure that the pretreated three-dimensional alumina fiber fabric is completely immersed in the second sol with added initiator, and continue to evacuate to a vacuum pressure of -0.09 5MPa environment for 75min, take out and dry at 65℃ for 6h, take out and completely immerse in anhydrous ethanol, stand at 40℃ for 60h, replace anhydrous ethanol once every 12h, take out and add to a supercritical drying kettle, control the temperature of the supercritical drying kettle to 270℃ and the pressure to 9MPa under nitrogen atmosphere, keep the temperature and pressure for 2h, release the gas and cool naturally to room temperature, take out and stand at 650℃ for 2.5h to obtain the fiber fabric after secondary impregnation;

[0086] 6. Vapor deposition: Add the fiber fabric after the second impregnation into a chemical vapor deposition furnace, evacuate the chamber, heat the temperature to 900°C at a rate of 25°C / min, introduce BCl3, NH3, H2, and Ar into the reaction chamber, control the introduction rate of BCl3 to 1L / min, the introduction rate of NH3 to 4L / min, the introduction rate of H2 to 5L / min, and the introduction rate of Ar to 5L / min, and feed the gas for 35 minutes to obtain a reusable flexible aerogel composite material with hydrophobic properties resistant to 800°C.

[0087] Example 3

[0088] A method for preparing a reusable flexible aerogel composite material with hydrophobic properties resistant to 800°C, specifically comprising:

[0089] 1. Preparation of the first sol:

[0090] (1) Preparation of surface modified aluminum oxide whisker suspension: 120 g aluminum oxide whisker, 35 g polysorbate 80 and 2500 mL deionized water were mixed, stirred at room temperature at a stirring speed of 200 rpm for 4 h, centrifuged, and the precipitate was taken out and washed with deionized water for 4 times. After vacuum drying, it was mixed with 1300 mL deionized water and ultrasonically vibrated at a frequency of 25 kHz for 35 min to obtain a surface modified aluminum oxide whisker suspension;

[0091] The average length of the aluminum oxide whiskers is 10 μm and the average diameter is 0.5 μm;

[0092] (2) Mixing: 420 mL of tetraethyl orthosilicate, 2100 mL of anhydrous ethanol, and 180 mL of deionized water were mixed, and stirred at 200 rpm for 15 min at room temperature. A 0.1 mol / L hydrochloric acid aqueous solution was added to adjust the pH to 4, and stirred for 2.5 h. 140 mL of the surface-modified alumina whisker suspension was added dropwise at a dropping speed of 5 mL / min. After the addition was completed, stirring was continued for 40 min to obtain a first sol.

[0093] 2. Preparation of the second sol:

[0094] (1) Preparation of surface-modified nano-aluminum oxide whisker suspension: 120 g of nano-aluminum oxide whisker, 50 g of polysorbate 80, and 3200 mL of deionized water were mixed, stirred at room temperature at a stirring speed of 200 rpm for 4 h, centrifuged, and the precipitate was taken out and washed with deionized water for 4 times. After vacuum drying, it was mixed with 1800 mL of deionized water and ultrasonically vibrated at a frequency of 25 kHz for 50 min to obtain a surface-modified nano-aluminum oxide whisker suspension;

[0095] The average length of the nano-aluminum oxide whiskers is 200 nm and the average diameter is 10 nm;

[0096] (2) Mixing: 420 mL of tetraethyl orthosilicate, 2100 mL of anhydrous ethanol, and 180 mL of deionized water were mixed, and stirred at room temperature at a stirring speed of 200 rpm for 15 min. A 0.1 mol / L hydrochloric acid aqueous solution was added to adjust the pH to 4, and stirred for 2.5 h. 200 mL of the surface-modified nano-alumina whisker suspension was added dropwise at a dropping speed of 6 mL / min. After the addition was completed, stirring was continued for 40 min to obtain a second sol.

[0097] 3. Pretreatment: The three-dimensional alumina fiber fabric was completely immersed in a 5wt% polyethylene glycol 400 aqueous solution, allowed to stand at room temperature for 5h, taken out, washed 4 times with deionized water, and vacuum dried to obtain the polyethylene glycol-treated fiber fabric. 520g of the polyethylene glycol-treated fiber fabric, 1600mL of 1,2-butanediol, 1050mL of 3-aminopropyltrimethoxysilane, and 20g of p-toluenesulfonic acid were mixed, stirred at 95°C at a stirring speed of 300rpm for 40min, stirred at 155°C for 9h, the three-dimensional alumina fiber fabric was taken out, washed 4 times with deionized water, washed 4 times with anhydrous ethanol, and allowed to stand for 40min at a temperature of 60°C and a pressure of 2kPa to obtain the pretreated three-dimensional alumina fiber fabric;

[0098] The fiber volume fraction in the three-dimensional alumina fiber fabric is 40%;

[0099] 4. One-time impregnation: Add the pretreated three-dimensional alumina fiber fabric into the mold, then put it into a vacuum tank, evacuate to a vacuum pressure of -0.1MPa, let it stand for 40 minutes, then add 1mol / L ammonia water to the first sol to adjust the pH to 7 to obtain the first sol with added initiator, add the first sol with added initiator into the vacuum tank to ensure that the pretreated three-dimensional alumina fiber fabric is completely immersed in the first sol with added initiator, and continue to evacuate to a vacuum pressure of -0.1M Pa environment for 60 minutes, take out and dry at 70 ° C for 8 hours, take out and completely immerse in anhydrous ethanol, stand at 60 ° C for 72 hours, replace anhydrous ethanol once every 12 hours, take out and add to a supercritical drying kettle, control the temperature of the supercritical drying kettle to 280 ° C and the pressure to 10 MPa under a nitrogen atmosphere, keep the temperature and pressure for 3 hours, release the gas and naturally cool to room temperature, take out and stand at a temperature of 700 ° C for 2 hours, and obtain a fiber fabric after one immersion;

[0100] 5. Secondary impregnation: add the fiber fabric after the primary impregnation into the mold, then put it into the vacuum tank, evacuate to the vacuum pressure of -0.1MPa, let it stand for 40min, then add ammonia water with a concentration of 1mol / L to the second sol to adjust the pH to 7, and obtain the second sol with the addition of the initiator, add the second sol with the addition of the initiator into the vacuum tank, ensure that the pretreated three-dimensional alumina fiber fabric is completely immersed in the second sol with the addition of the initiator, continue to stand for 80min under the vacuum pressure of -0.1MPa, take it out and dry it at 70°C for 8h, take it out and completely immerse it in anhydrous ethanol, let it stand at 60°C for 72h, replace the anhydrous ethanol once every 12h, take it out and add it to the supercritical drying kettle, control the temperature of the supercritical drying kettle to 280°C and the pressure to 10MPa under nitrogen atmosphere, keep the temperature and pressure for 3h, release the gas and naturally cool it to room temperature, take it out and let it stand for 3h at a temperature of 700°C, and obtain the fiber fabric after the secondary impregnation;

[0101] 6. Vapor deposition: Add the fiber fabric after the second impregnation into a chemical vapor deposition furnace, evacuate the chamber, heat it to 1000°C at a heating rate of 30°C / min, introduce BCl3, NH3, H2, and Ar into the reaction chamber, control the introduction rate of BCl3 to 1.2L / min, the introduction rate of NH3 to 4.8L / min, the introduction rate of H2 to 5L / min, and the introduction rate of Ar to 5L / min, and feed the gas for 40 minutes to obtain a reusable flexible aerogel composite material with hydrophobic properties resistant to 800°C.

[0102] Comparative Example 1

[0103] Based on the preparation method of the 800°C resistant and hydrophobic reusable flexible aerogel composite material of Example 2, adjustments are made. The specific adjustments are: omitting the first step of preparing the first sol and the fourth step of the one-time impregnation.

[0104] Comparative Example 2

[0105] Based on the preparation method of the 800°C resistant and hydrophobic reusable flexible aerogel composite material of Example 2, adjustments are made. The specific adjustments are: omitting the second sol preparation step in step 2 and the secondary impregnation step in step 5.

[0106] Comparative Example 3

[0107] Based on the preparation method of the 800° C. resistant and reusable flexible aerogel composite material of Example 2, adjustments are made. The specific adjustments are: omitting the third pretreatment step.

[0108] Performance Testing

[0109] The compressive strength, tensile strength, room temperature wetting angle, room temperature wetting angle after treatment at 800°C for 2 hours, room temperature thermal conductivity, thermal conductivity at 800°C, and room temperature thermal conductivity after treatment at 800°C for 2 hours of the flexible aerogel composite materials prepared in Examples 1-3 and Comparative Examples 1-3 were tested, and the test results are shown in Table 1:

[0110] Table 1

[0111]

[0112] It can be seen from the performance test results that by preparing the first sol and using the first sol for one impregnation, the compressive strength and tensile strength of the flexible aerogel composite material can be improved, and the thermal conductivity at room temperature, the thermal conductivity at 800°C, and the thermal conductivity at room temperature after treatment at 800°C for 2 hours can be reduced.

[0113] By preparing a second sol and using the second sol for secondary impregnation, the compressive strength, tensile strength, and room-temperature wetting angle of the flexible aerogel composite material after treatment at 800°C for 2 hours can be improved, and the thermal conductivity at 800°C and room-temperature thermal conductivity after treatment at 800°C for 2 hours can be reduced.

[0114] By pretreatment, the compressive strength and tensile strength of the flexible aerogel composite material can be improved, and the thermal conductivity at room temperature, the thermal conductivity at 800°C, and the thermal conductivity at room temperature after treatment at 800°C for 2 hours can be reduced.

[0115] The method for preparing the first sol includes preparing a surface-modified alumina whisker suspension and mixing, wherein the surface-modified alumina whisker suspension is prepared by using polysorbate 80 to perform surface modification on alumina whiskers to improve the dispersibility of the alumina whiskers, thereby obtaining a surface-modified alumina whisker suspension, and then dispersing the surface-modified alumina whisker suspension in the hydrolyzed silica sol to obtain a first sol. Then, in one impregnation, the pretreated three-dimensional alumina fiber fabric is impregnated with the first sol. On the one hand, the surface-modified alumina whiskers can improve the bonding strength between the silica sol and the pretreated three-dimensional alumina fiber fabric; on the other hand, the surface-modified alumina whiskers can play a role in improving the strength and toughness of the silica sol.

[0116] The method for preparing the second sol includes preparing a surface-modified nano-alumina whisker suspension and mixing, wherein the preparation of the surface-modified nano-alumina whisker suspension is to use polysorbate 80 to modify the surface of the nano-alumina whiskers to improve the dispersibility of the nano-alumina whiskers to obtain the surface-modified nano-alumina whisker suspension, and then disperse the surface-modified nano-alumina whisker suspension in the hydrolyzed silica sol to obtain the second sol. Then, in the secondary impregnation, the second sol is used to impregnate the fiber fabric after the first impregnation. The surface-modified nano-alumina whiskers can exist on the surface of the flexible aerogel composite material. On the first hand, the surface-modified nano-alumina whiskers can improve the strength and toughness of the silica sol; on the second hand, the surface-modified nano-alumina whiskers can improve the thermal stability of the silica sol and improve the internal bonding strength of the silica sol, avoiding the powdering problem of the silica aerogel; on the third hand, the surface-modified nano-alumina whiskers can increase the surface area of ​​the surface silica aerogel, improve the adsorption of the surface silica aerogel, and promote the chemical deposition of the boron nitride hydrophobic coating.

[0117] Micron-sized alumina whiskers and nano-sized alumina whiskers are introduced respectively through a combination of primary impregnation and secondary impregnation. Micron-sized alumina whiskers are distributed in the inner layer for toughening and improving compatibility, and nano-sized alumina whiskers are distributed in the outer layer for toughening and improving thermal stability, internal bonding strength, and the density of the hydrophobic coating, thereby improving the strength, flexibility, hydrophobicity, durability, and high temperature resistance of the aerogel composite material.

[0118] The pretreatment method is to first use polyethylene glycol 400 to surface treat the three-dimensional alumina fiber fabric to improve the wettability of the surface of the three-dimensional alumina fiber fabric, and then use 1,2-butanediol and 3-aminopropyltrimethoxysilane to graft silicon-carbon side chains on the surface of the three-dimensional alumina fiber fabric. Polyethylene glycol 400 is bonded to the silicon-carbon side chains, thereby improving the bonding strength between the three-dimensional alumina fiber fabric and the silica sol and the surface-modified alumina whisker suspension, promoting the dispersion of the silica sol, and thus the strength, flexibility, durability, and high temperature resistance of the aerogel composite material.

[0119] Unless otherwise specified, all percentages used in the present invention are by mass.

[0120] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a reusable flexible aerogel composite material with hydrophobic properties resistant to 800°C, characterized in that: The method comprises the following steps: preparing a first sol, preparing a second sol, pre-treating, first dipping, second dipping, and vapor deposition; The preparation of the first sol comprises the following steps: preparing a surface-modified aluminum oxide whisker suspension, mixing; The method for preparing the surface-modified aluminum oxide whisker suspension comprises: mixing aluminum oxide whiskers, polysorbate 80, and a first portion of deionized water, stirring at room temperature, centrifuging, taking a precipitate, washing, vacuum drying, mixing with a second portion of deionized water, and ultrasonically vibrating to obtain a surface-modified aluminum oxide whisker suspension; The preparation of the first sol is mixed: ethyl orthosilicate, anhydrous ethanol and deionized water are mixed, stirred at room temperature, the pH is adjusted to 3-4, stirred, and the surface modified aluminum oxide whisker suspension is added dropwise, and stirring is continued after the addition is completed to obtain the first sol; The preparation of the second sol comprises the following steps: preparing a surface-modified nano-aluminum oxide whisker suspension, mixing; The method for preparing the surface-modified nano-aluminum oxide whisker suspension comprises: mixing the nano-aluminum oxide whisker, polysorbate 80 and the first portion of deionized water, stirring at room temperature, centrifuging, taking the precipitate, washing, vacuum drying, mixing with the second portion of deionized water, and ultrasonically vibrating to obtain the surface-modified nano-aluminum oxide whisker suspension; The preparation of the second sol is as follows: ethyl orthosilicate, anhydrous ethanol and deionized water are mixed, stirred at room temperature, the pH is adjusted to 3-4, stirred, and the surface modified nano-aluminum oxide whisker suspension is added dropwise, and stirring is continued after the addition is completed to obtain the second sol; The pretreatment comprises: completely immersing the three-dimensional alumina fiber fabric in a polyethylene glycol 400 aqueous solution, standing at room temperature, taking out, washing, and vacuum drying to obtain the fiber fabric treated with polyethylene glycol; mixing the fiber fabric treated with polyethylene glycol, 1,2-butanediol, 3-aminopropyltrimethoxysilane, and p-toluenesulfonic acid, stirring at 90-95° C., stirring at 150-155° C., taking out the three-dimensional alumina fiber fabric, washing, and standing to obtain the pretreated three-dimensional alumina fiber fabric.

2. The method for preparing the reusable flexible aerogel composite material with 800°C hydrophobic resistance according to claim 1, characterized in that: In the preparation of the surface-modified aluminum oxide whisker suspension, the mass volume ratio of the aluminum oxide whisker, polysorbate 80, the first portion of deionized water, and the second portion of deionized water is 100-120 g: 30-35 g: 2200-2500 mL: 1200-1300 mL; The average length of the aluminum oxide whiskers is 10 μm, and the average diameter is 0.5 μm.

3. The method for preparing the reusable flexible aerogel composite material with 800°C hydrophobic resistance according to claim 1, characterized in that: In the mixing for preparing the first sol, the volume ratio of ethyl orthosilicate, anhydrous ethanol, deionized water, and surface-modified alumina whisker suspension is 400-420:1800-2100:160-180:120-140; The drop rate of the surface modified aluminum oxide whisker suspension is 4-5 mL / min.

4. The method for preparing the reusable flexible aerogel composite material with 800°C hydrophobic resistance according to claim 1, characterized in that: In the preparation of the surface-modified nano-aluminum oxide whisker suspension, the mass volume ratio of the nano-aluminum oxide whisker, polysorbate 80, the first portion of deionized water, and the second portion of deionized water is 100-120 g: 45-50 g: 2900-3200 mL: 1600-1800 mL; The average length of the nano-aluminum oxide whisker is 200 nm, and the average diameter is 10 nm.

5. The method for preparing the reusable flexible aerogel composite material with 800°C hydrophobic resistance according to claim 1, characterized in that: In the mixing for preparing the second sol, the volume ratio of ethyl orthosilicate, anhydrous ethanol, deionized water, and surface-modified nano-aluminum oxide whisker suspension is 400-420:1800-2100:160-180:170-200; The drop speed of the surface modified nano-aluminum oxide whisker suspension is 5-6 mL / min.

6. The method for preparing the reusable flexible aerogel composite material with 800°C hydrophobic resistance according to claim 1, characterized in that: In the pretreatment, the mass volume ratio of the polyethylene glycol-treated fiber fabric, 1,2-butanediol, 3-aminopropyltrimethoxysilane, and p-toluenesulfonic acid is 500-520 g: 1500-1600 mL: 950-1050 mL: 15-20 g; The concentration of the polyethylene glycol 400 aqueous solution is 5wt%; The fiber volume fraction in the three-dimensional alumina fiber fabric is 40%; The static temperature is 55-60° C., the pressure is 1-2 kPa, and the time is 35-40 min.

7. The method for preparing the reusable flexible aerogel composite material with 800°C hydrophobic resistance according to claim 1, characterized in that: The primary impregnation comprises: performing vacuum pretreatment on the pretreated three-dimensional alumina fiber fabric, then completely immersing it in the first sol with the initiator added thereto for vacuum treatment, drying, taking it out and completely immersing it in anhydrous ethanol for aging, taking it out and performing supercritical drying, releasing the gas after the supercritical drying and naturally cooling it to room temperature, taking it out and allowing it to stand, and obtaining the fiber fabric after the primary impregnation; In the first dipping, the preparation method of the first sol with the added initiator is: adding ammonia water to the first sol to adjust the pH to 6-7, so as to obtain the first sol with the added initiator; The vacuum pretreatment has a vacuum pressure of -0.095 MPa to -0.1 MPa and a time of 30-40 min; The vacuum pressure of the vacuum treatment is -0.095MPa to -0.1MPa, and the time is 50-60min; The drying temperature is 50-70°C and the drying time is 5-8h; The aging temperature is 30-60° C., the time is 48-72 hours, and the anhydrous ethanol is replaced once every 12 hours during the aging process; The supercritical drying is carried out in a nitrogen atmosphere at a temperature of 260-280° C., a pressure of 8-10 MPa, and a time of 1-3 h; The standing temperature is 600-700° C. and the standing time is 1.5-2 hours.

8. The method for preparing the reusable flexible aerogel composite material with 800°C hydrophobic resistance according to claim 1, characterized in that: The secondary impregnation: vacuum pretreatment is performed on the fiber fabric after the primary impregnation, and then the fiber fabric is completely immersed in the second sol with the initiator for vacuum treatment, dried, taken out and completely immersed in anhydrous ethanol for aging, taken out and subjected to supercritical drying, after the supercritical drying is completed, the gas is released and the temperature is naturally lowered to room temperature, taken out and allowed to stand, and the fiber fabric after the secondary impregnation is obtained; In the secondary impregnation, the second sol with the initiator added is prepared by: adding ammonia water to the second sol to adjust the pH to 6-7 to obtain the second sol with the initiator added; The vacuum pretreatment has a vacuum pressure of -0.095 MPa to -0.1 MPa and a time of 30-40 min; The vacuum pressure of the vacuum treatment is -0.095MPa to -0.1MPa, and the time is 70-80min; The drying temperature is 60-70°C and the drying time is 5-8h; The aging temperature is 30-60° C., the time is 48-72 hours, and the anhydrous ethanol is replaced once every 12 hours during the aging process; The supercritical drying is carried out in a nitrogen atmosphere at a temperature of 260-280° C., a pressure of 8-10 MPa, and a time of 1-3 h; The standing temperature is 600-700° C. and the standing time is 2-3 hours.

9. The method for preparing the reusable flexible aerogel composite material with 800°C hydrophobic resistance according to claim 1, characterized in that: The vapor deposition is as follows: the fiber fabric after the secondary impregnation is added into a chemical vapor deposition furnace, vacuumized, heated to 800-1000°C, BCl3, NH3, H2, and Ar are introduced into the reaction chamber, and the gas is supplied for 30-40 minutes to obtain a flexible aerogel composite material with hydrophobic properties resistant to 800°C and reusable.

10. The method for preparing the reusable flexible aerogel composite material with 800°C hydrophobic resistance according to claim 9, characterized in that: In the vapor deposition, the heating rate to 800-1000°C is 25-30°C / min; The introduction rate of the BCl3 is 0.8-1.2 L / min, the introduction rate of the NH3 is 3.2-4.8 L / min, the introduction rate of the H2 is 5 L / min, and the introduction rate of the Ar is 5 L / min.